The Use of Code Mixing in the Japanese Viral Song Entitled “Shinunoga E-Wa” - Kireina Fernanda Utomo; Ismatul Khasanah (Universitas Muhammadiyah Yogyakarta, 2023)
Numerous languages are spoken in various countries. It is widely acknowledged that English holds the status of a worldwide language. English is frequently employed as a language of code mixing within the context of musical compositions. In the viral Japanese song titled